2014
DOI: 10.1021/ic500449d
|View full text |Cite
|
Sign up to set email alerts
|

Valence State Driven Site Preference in the Quaternary Compound Ca5MgAgGe5: An Electron-Deficient Phase with Optimized Bonding

Abstract: The quaternary phase Ca 5 Mg 0.95 Ag 1.05(1) Ge 5 (3) was synthesized by high-temperature solid-state techniques, and its crystal structure was determined by single-crystal diffraction methods in the orthorhombic space group Pnma -Wyckoff sequence c 12 with a = 23.1481(4) Å, b = 4.4736(1) Å, c = 11.0128(2) Å, V = 1140.43(4) Å 3 , Z = 4. The crystal structure can be described as linear intergrowths of slabs cut from the CaGe (CrB-type) and the CaMGe (TiNiSi-type; M = Mg, Ag) structures. Hence, 3 is a hettotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Eu 2– x Mg 2– y Ge 3 ( x = 0.1; y = 0.5) represents an interesting case for which the electron deficiency is triggered by geometrical requirements, i.e., a high density of cations resulting in defects at cation sites. Recently, we observed that one‐electron deficiency in the quasi‐ternary phase Ca 5 MgAgGe 5 is the result of local symmetry breaking of the Ge 4 chains from C 2 h to C s which is caused by Ag/Mg partial ordering as dictated by higher Madelung's part in the lattice energy 18…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eu 2– x Mg 2– y Ge 3 ( x = 0.1; y = 0.5) represents an interesting case for which the electron deficiency is triggered by geometrical requirements, i.e., a high density of cations resulting in defects at cation sites. Recently, we observed that one‐electron deficiency in the quasi‐ternary phase Ca 5 MgAgGe 5 is the result of local symmetry breaking of the Ge 4 chains from C 2 h to C s which is caused by Ag/Mg partial ordering as dictated by higher Madelung's part in the lattice energy 18…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, targeted synthesis of novel Zintl polyanions may be achievable through appropriate mixtures of chemically diverse cationic species in an adequate ratio. Such a paradigm is well reflected in the recently discovered structure series Ca 2+ n Ag 2+ x Ge 2– x + n ,17,18 in which the polarizing Ag + cation can be partially substituted by divalent Mg or trivalent Al. It represents the Ca sub‐family of the broader structural homology A 2+ n T 2 X 2+ n ( X = Si, Ge, Sn; T = transition metal; A = electropositive s ‐metal), which were rationalized by Zhao and Parthé (1989)19 as intergrowths of fragments cut from the TiNiSi‐ and the CrB‐type structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] Partial mixing of Mg and Ag in Ca 5 MgAgGe 5 also results in Ca-Ag/Mg distances between 3.18 and 3.30 Å. [26] The bridging atoms, Mg or Ag, are in turn surrounded by eight Ca in their second coordination sphere in a strongly distorted square prismatic arrangement ( Figure 1c). This is in contrast to Pd or Pt atoms forming the dimers that are each surrounded by six Ca atoms in a distorted trigonal prismatic environment with Ca-Pd/Pt distances as short as 2.966(2) or 2.975(1) Å in Ca 2 AgPd 2 or Ca 2 AgPt 2 .…”
Section: Dedicated Clustermentioning
confidence: 99%